2011
DOI: 10.1149/1.3559754
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Off-State Leakage Current in In0.7Ga0.3As Channel n-MOSFETs with Self-Aligned Ni-InGaAs Contact Metallization

Abstract: In 0.7 Ga 0.3 As channel n-MOSFETs (metal-oxide-semiconductor field-effect transistors) with Si-doped S/D and self-aligned NiInGaAs contact were demonstrated for the first time. The salicide-like metallization process employed a direct reaction between Ni and Si-doped InGaAs, followed by the removal of the unreacted Ni. As compared with n-MOSFETs with metallic Ni-InGaAs S/D (i.e. no Si doping in S/D), n-MOSFETs with Ni-InGaAs contact formed on Si-doped S/D show significantly improved OFFstate current I OFF in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 23 publications
1
12
0
Order By: Relevance
“…R □ drastically decreases after RTA and the values as low as 25 /□ are obtained even in the samples with t Ni-InGaAs = 6 nm (t Ni = 4 nm, T a < 250˚C). This value is low enough for scaled metal S/D devices and almost the same as that of previous reports [3,4] in spite of the fact that t Ni-InGaAs in this study is much thinner. From these results, it can be confirmed that thin Ni-InGaAs alloyed layers with low R □ , which meets the requirement of scaled metal S/D MOSFETs, are formed through the control of t Ni and T a .…”
Section: Introductionsupporting
confidence: 89%
See 1 more Smart Citation
“…R □ drastically decreases after RTA and the values as low as 25 /□ are obtained even in the samples with t Ni-InGaAs = 6 nm (t Ni = 4 nm, T a < 250˚C). This value is low enough for scaled metal S/D devices and almost the same as that of previous reports [3,4] in spite of the fact that t Ni-InGaAs in this study is much thinner. From these results, it can be confirmed that thin Ni-InGaAs alloyed layers with low R □ , which meets the requirement of scaled metal S/D MOSFETs, are formed through the control of t Ni and T a .…”
Section: Introductionsupporting
confidence: 89%
“…One of the critical challenges in InGaAs MOSFETs is a formation of low resistance S/D contacts by a self-aligned manner. Recently, a SALICIDE-like contact technology using Ni-InGaAs alloy has been proposed and metal S/D InGaAs nMOSFETs with very low Schottky barrier height have been demonstrated [3,4]. However, thickness controllability and thermal stability of those alloyed layers have not been well investigated yet.…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12][13] Ni has been used as a contact metal for InGaAs MOSFETs in early work. [20][21][22][23] Ni-InGaAs, which forms an Ohmic contact on n-type InGaAs, can be obtained by a direct reaction between deposited Ni and InGaAs. The presence of Ni at the contact interface with InGaAs improves adhesion between the gold-based alloy and InGaAs, and also promotes interaction between them during metallization.…”
Section: Introductionmentioning
confidence: 99%
“…[14][15][16] It has been employed in Au-Ge and Au-Sn metallization for forming nonself aligned Ohmic contacts on n-InGaAs or in Au-Zn metallization for forming Ohmic contacts on p-InGaAs. 22,24 Although the metallurgy of the reaction between Ni and GaAs has been extensively reported, [25][26][27] there is a lack of studies on the specifics of Ni reaction with InGaAs to form Ni-InGaAs. [17][18][19] More recently, Ni-InGaAs has been proposed as a candidate for self-aligned contact material for InGaAs.…”
Section: Introductionmentioning
confidence: 99%
“…were the first to report on a self‐aligned ohmic contact metal process for III–V MOSFET on the basis of the epitaxial growth of GeSi on n + GaAs and subsequent Ni deposition, forming a low‐resistivity germano‐silicide (NiGeSi) with good morphology . The use of InGaAs as the III–V channel material facilitates a more simplified metallization scheme on the basis of Ni deposition, which can be readily annealed at low temperature to form a low‐resistivity self‐aligned Ni‐InGaAs quaternary alloy …”
Section: Resultsmentioning
confidence: 99%